HUBUNGAN PERILAKU SPIRITUAL DENGAN PERILAKU BERPACARAN PADA REMAJA DI SMAN 1 JENGGAWAH KABUPATEN JEMBER - Astutik, Windy; Indriyani, Diyan; Kholifah, Siti (The Indonesian Journal of Health Science, 2017)
Introduction: The spiritual behavior during the teenage time allows emotional shock, anxiety, and worries that cause teenagers to show any behaviors that represent  their  own  mind,  like  the  dating  behavior.  Method:  This research employs correlational design by using cross sectional approach which is intended to analyze the correlation between spiritual behavior and dating behavior of the teenagers. The population of this research is theX and XI grade students at SMAN 1 JenggawahJember Regency, numbering 462 individuals. As many as 214 respondents  are  taken as  the sample  of the research  by using  Proportionate Stratified Random Sampling technique. Result: Results of the research reveal that majority  of  the  respondents  show  good  spiritual  behavior  as  shown  by  187 (87,4%) respondents, whereas 27 (12,6%) respondents show poor spiritual behavior. As many as 185 (86,4%) respondents show no deviant behavior as opposed to 29 (13,6%) respondents who show deviant behavior. The statistical testing conducted by using Fisher Exact Test (?=0,05) results in the correlation between spiritual behavior and dating  behavior as illustrated by the p value 0,000?0,05. The conclusion of this research states that the correlation between spiritual   behavior   and dating behavior of   the   teenagers at SMAN 1 JenggawahJember Regency exists. Discuss: This research recommends that parents hold effective communication with teenagers for at least 15 minutes per day, respectively.Keywords: Spiritual Behavior; Dating Behavior; Teenager